Technological transformation and nonbank competition in a model of retail banking oligopoly - Jukka Vesala (Bank of Finland, 1998)
A model of banking competition is developed, in which diffusion of electronic banking (eg pc and phone banking) and nonbank competition (eg mutual funds, retail stores and insurance firms) are studied as factors that diminish the benefits of branch and ATM networks in terms of enhanced demand and pricing power.A structural increase in price competition, a decrease in the variation of loan and deposit rates across banks and a decline in the optimal numbers of branches and ATMs is shown to result. Competition increases permanently unless banks are able to redifferentiate from rivals through novel innovation that compensates for the reduced value of network differentatiation. Capacity collusion is shown to reduce the sizes of branch and ATM networks as well as banks' markups of loan and deposit rates over the money market rate and respective marginal operating costs.ATM compatibility reduces the total number of machines and under certain conditions raises deposit rates. Under strategic complementarity technological transformation and nonbank expansion enhance the transmission of monetary policy into lending rates, as well as into deposit rates, because banks' incentives to change their rates and the sizes of optimal responses increase with respect to changes in the money market rate.If these trends continue to be more pronounced
URN:NBN:fi:bof-20140807630
Keywords: 330